UV-Spectrophotometric Determination of Tenatoprazole from its Bulk and Tablets - M. SUGUMARAN,; R.NAGESWARA RAO,; D. JOTHIESWARI, (International Journal of Pharma and Bio Sciences, 2010)
A simple , rapid, sensitive and accurate UV-spectrophotometric method has been developed for estimation of Tenatoprazole from Pharmaceutical formulation. In 0.1N NaOH, Tenatoprazole showed absorbance maxima at 314nm. Linearity was observed in the concentration range of 2-12 µg/ml (r2 =0.999).The amount of drug estimated from the formulation was found to be in the good agreement with label claim. The recovery studies were carried out at three different levels i.e. at 50%100% and 125%. The method was validated statistically.